Management of paediatric immune thrombocytopaenia in a South African centre from 1991-2011 - Akhalwaya, Shehnaaz (Department of Paediatrics and Child Health, 2017)
Three hundred and seventeen patients meeting the diagnostic criteria for immune thrombocytopenia presented to Red Cross War Memorial Children's Hospital between 1991 and 2011. We retrospectively reviewed these patients in order to describe patient demography, the natural history of the disease, and different approaches to diagnosis and management. There were 162 males and 155 female patients. The median age of onset was 3.48 years old (IQR 1.66-6.36). In the 4 weeks preceding presentation, 98 (31%) patients had a viral illness. The median presenting platelet count was 7 x 109/L (IQR 3-14.5). Petechiae were the most common clinical sign at presentation (58%; 184/317). None of the patients presented with intracranial haemorrhages. The majority of patients in the study were admitted (234/317; 74%) with a median stay of 4 days (IQR 0-6). Bone marrow aspirates (BMA) were performed in 188 patients (59%). There was a reduction in BMA from 1991-2000 to 2001-2011 (p<0.001). There was an increase in the percentage of patients treated from 1991-2000 (77/170; 44%) to 2001-2011 (99/147, 67% p< 0.001). Resolution occurred in 75% of patients with a median time to resolution of 31 days (IQR 11-73 days). When we analysed the "survival estimate" from the 2 decades, despite differing rates of BMA, treatment rates and regimens, there was no statistical difference in resolution.